2009
DOI: 10.1007/s00535-009-0110-2
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog relates to colorectal carcinogenesis

Abstract: This result indicates that Shh-related carcinogenesis and Shh expression may be a trigger for the adenoma-carcinoma sequence. This study suggests a potential therapeutic target of hedgehog blockade in carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 22 publications
10
76
1
Order By: Relevance
“…He did not observe expression of GLI1 protein in the stroma, indicating that the stroma did not have an active Hh-GLI signaling (Varnat et al, 2009). Yoshikawa found that colorectal adenomas expressed SHH more frequently compared with normal mucosa and adenocarcinoma, which suggested that SHH expression might increase during carcinogenesis and then decrease during tumor progression in the adenoma-carcinoma sequence (Yoshikawa et al, 2009). By contrast, in a clinical study for SHH, IHH and GLI1 genes in 36 CRC patients, Fu found the expressions of SHH and GLI1 proteins were increased significantly in tumor tissues compared with those in hyperplastic polyps and colorectal adenomas.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…He did not observe expression of GLI1 protein in the stroma, indicating that the stroma did not have an active Hh-GLI signaling (Varnat et al, 2009). Yoshikawa found that colorectal adenomas expressed SHH more frequently compared with normal mucosa and adenocarcinoma, which suggested that SHH expression might increase during carcinogenesis and then decrease during tumor progression in the adenoma-carcinoma sequence (Yoshikawa et al, 2009). By contrast, in a clinical study for SHH, IHH and GLI1 genes in 36 CRC patients, Fu found the expressions of SHH and GLI1 proteins were increased significantly in tumor tissues compared with those in hyperplastic polyps and colorectal adenomas.…”
Section: Discussionmentioning
confidence: 93%
“…PTCH was not expressed in colon tumor cell lines (0/11), although a few of these cell lines expressed GLI1 in the absence of PTCH. As PTCH and GLI1 were indicators of Hh pathway activity, He concluded that the Hh pathway was not active in these CRC cell lines (Yoshikawa et al, 2009). Chatel analyzed the gene and protein expressions DOI:http://dx.doi.org/10.7314/APJCP.2012.13.5.2319 of the main key members of the Hh pathway (SHH, IHH, PTCH, SMO, GLI1, GLI2, GLI3, SUFU and HHIP) in 7 colon cancer cell lines and found none of them expressed the complete set of Hh pathway members (Chatel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gli1 is a transcriptional activator [18] , which induces the expression of numerous target genes that regulates proliferation, differentiation, and extracellular matrix interactions [19,20] . Increasing evidence has demonstrated that the Hh signaling pathway plays an important role in multiple tumor types, for example, basal cell carcinoma [21,22] , pancreatic cancer [23] , colon carcinoma [24] , gastric cancer [25] , small cell lung cancer [26] , prostate cancer [27][28][29] , breast cancer [30,31] , early childhood hepatoblastoma [32] , and esophageal cancers [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Expression of IHH, which is included in the differentiation of enterocytes, has been suggested to be lost in early phases of human colorectal carcinogenesis (van den Brink et al 2004). It is suggested, however, that Hh signaling increases with colon cancer progression (Yoshikawa et al 2009). It was found further that Hh signaling components are actually activated in advanced human colon cancer cells and their CSCs, where GLI1 expression was higher in CD133 ?…”
Section: Hedgehog (Hh) Pathwaymentioning
confidence: 99%